1977
DOI: 10.1111/j.1365-2494.1977.tb01414.x
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen fixation by white clover in hill pasture

Abstract: An experiment is described in which the amount of nitrogen fixed by the white clover component of a surface-sown hill sward was determined using small quantities of "N-labelled ammonium sulphate. Between 11 July and 22 August 1974 25 kg ha-' N was fixed. No evidence of a transfer of N from clover to the associated perennial ryegrass was detectable over this period although the N content of the grass growing with the clover was higher. The relative advantages of the isotope technique and the acetylene reduction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
29
0

Year Published

1983
1983
1996
1996

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(35 citation statements)
references
References 23 publications
6
29
0
Order By: Relevance
“…This potential was similar to that found in similar types of grassland elsewhere in the U.K. (Haystead & Lowe, 1977) and probably contributes significantly to the maintenance ofthe soil nitrogen pool.…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…This potential was similar to that found in similar types of grassland elsewhere in the U.K. (Haystead & Lowe, 1977) and probably contributes significantly to the maintenance ofthe soil nitrogen pool.…”
Section: Discussionsupporting
confidence: 57%
“…Although long-term estimates of nitrogen fixation are very imprecise if the data from short term C2H2-reduction incubations are used, the calculated amounts were similar to those published elsewhere (e.g. Haystead & Lowe, 1977). It was found that lichens (found on site 1 only) can fix up to 6 g N ha-h-(measured in October) if the ground is sufficiently wet.…”
Section: The Contribution Of Nitrogen Jixation To the Soil Nitrogen Bmentioning
confidence: 92%
“…Walker et al (1954) detected 'excretion' of N by underground organs of clover in variable, but sometimes large, quantities. Haystead and Lowe (1977) found evidence of total N increase in grass companion plants, as have other workers, but did not detect differences in isotope ratio between companionand monoculture-grasses. This result has led Haystead and Marriott (1979) and Haystead (1983) to believe that N from decaying nodules is immobilized by the rhizophere microflora, delaying the changes in isotope ratio.…”
Section: Discussionmentioning
confidence: 59%
“…Of this indirect benefit 30.7 kgN ha -1 was accrued in the mixture grass by the end of the first growth period, falling to 8.3kgN h a -1 in the second growth period and only 3.7 kgN ha -1 in the third growth period. A 'N advantage' for grass growing in a mixture when compared to grass in a monoculture has been observed by many researchers working with grass/white clover pastures (Boiler and Nosberger, 1987;Cowling and Lockyer, 1966;Goodman and Collison, 1986;Haystead and Lowe, 1977;Munro and Davies, 1974;Simpson, 1976). Indeed, the more general idea of non-legume benefitting from association with legume was recognised by early workers (Lipman, 1912;Nicol, 1934).…”
Section: Discussionmentioning
confidence: 95%